Revisiting the Emergent Norm Theory to Understand Protest Communication in Social Media: the Improvisation-Verification-Solidification (IVS) Framework - Kwon, Hazel (AoIR Selected Papers of Internet Research, 2013)
Twitter has been discussed as a collective social awareness system during social crises. We revisit the classical theory of collective behavior, called the emergent norm theory by Killian and Turner (1987), to introduce the analytic framework that highlights major genres of protest communication activities in social media. In particular, we adapt the concept of “milling” and “keynoting” of Emergent Norm Theory and suggest that protest communication in social media can be categorized into three types: improvisation, verification, and solidification (IVS). Based on the analysis of Twitter usages during Jan 25th protest in Egypt, the validity of IVS framework is discussed in terms of the temporal and spatial differences of each communication genre.